(untitled) (Transactions on Additive Manufacturing Meets Medicine, 2021)
Three-dimensional printing is of critical importance in medical engineering and has been growing in recent years. Craniofacial reconstruction is currently shifting from autoplasty towards computer-aided planning and additive manufacturing, which primarily use titanium powders, selective laser melting, computer numeric controlled postmilling, and surface biofunctionalization. Of highest importance is the option to mirror the normal side of the face onto the damaged side and direct facial symmetry at the skeletal level. Restoration of normal, beautiful, and ideal contours is hindered by the preoperative appraisal of the response of the integument and the perception and expectations of the patient. Maurice Mommaerts is Professor and head, European Face Centre – University Hospital Brussels, Belgium, Coordinator Cleft & Craniofacial Team, University Hospital Brussels, Owner of OrthoFace Aesthetic Clinic, St. Martens-Latem, Consultant Facial Makeover Surgery, GZA & Face Ahead Clinic Antwerp, and Innovation ambassador at CADskills bv. Further Positions: Honorary past president European Association for Cranio-Maxillo-Facial Surgery; Founder and president Academy of Aesthetic Facial Surgery; Docent VUBrussels; Member of the Board of Directors, Aesthetic and Reconstructive Craniofacial Surgery Foundation, Hyderabad, Andrah Pradesh, India; Honorary Member of the Sociedad Española de Cirugía Plástica Facial; Fellow International College of Surgeons; Fellow American Academy of Cosmetic Surgery; Section editor for J Craniomaxillofac Surg, international editorial board member of Annals of Maxillofacial Surgery; Reviewer for J Craniofacial Surg, Ind J Plastic Surg, Am J Cosmetic Surgery.